Connecting Social, Clinical, and Home Care Services for Persons with Serious Illness in the Community. (10th May 2019) - Golden, Robyn L.; Emery‐Tiburcio, Erin E.; Post, Sharon; Ewald, Bonnie; Newman, Michelle
Abstract : The medical, psychological, cognitive, and social needs of older adults with serious illness are best met by coordinated and team‐based services and support. These services are best provided in a seamless care model anchored by integrated biopsychosocial assessments focused on what matters to older adults and their social determinants of health; individualized care plans with shared goals; care provision and management; and quality measurement with continuous improvement. This model requires (1) racially and ethnically diverse healthcare professionals, including mental health and direct service workers, with training in aging and team collaboration; (2) an integrated network of community‐based organizations (CBOs) providing in‐home services; (3) an electronic communication platform that spans the system of providers and organizations with skilled technology staff; and (4) payment models that incentivize team‐based care across the continuum of services, including CBOs, with adequate salaries and academic loan forgiveness to recruit and retain high‐quality team members. Assuring that this model is effective requires ongoing quality assurance measures that include not only quality of care and utilization data to demonstrate cost offsets of service integration, but also quality of life for both the older adults and the family members caring for them. Although this may seem a lofty ideal in comparison with our current fragmented system, we review models that provide the key elements effectively and cost efficiently. We then propose an Essential Care Model that defines best practice in meeting the needs of older adults with serious illness and their families. J Am Geriatr Soc 67:S412–S418, 2019.